2016
DOI: 10.1021/acs.langmuir.5b03677
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Stiffness of Multiple Particles Trapped by Dielectrophoretic Tweezers in a Microfluidic Device

Abstract: Characterization of the stiffness of multiple particles trapped by tweezers-based force spectroscopy is a key step in building simple, high-throughput, and robust systems that can investigate the molecular interactions in a biological process, but the technology to characterize it in a given environment simultaneously is still lacking. We first characterized the stiffness of multiple particles trapped by dielectrophoretic (DEP) tweezers inside a microfluidic device. In this characterization, we developed a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…It can be concluded that these movements of the trapped particles were from the thermal fluctuations (from Brownian motion) and have no significant impact on the capability of particle trapping within tested conditions [32,53,56,57]. These results show that the DEP trap force acting on the particle was also increased by an increase in the potential of the applied electric field, while the trapped particle remained close to the surface of the traps.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…It can be concluded that these movements of the trapped particles were from the thermal fluctuations (from Brownian motion) and have no significant impact on the capability of particle trapping within tested conditions [32,53,56,57]. These results show that the DEP trap force acting on the particle was also increased by an increase in the potential of the applied electric field, while the trapped particle remained close to the surface of the traps.…”
Section: Resultsmentioning
confidence: 93%
“…For the quantitative analysis of these movements of the trapped particles, experimental results described in Figs. 6 and 7 were used to compute DEP trap stiffness for the circular‐shape trap using the equipartition theorem [32]. The equipartition theorem is the simplest and straightforward method to determine trap stiffness from thermal fluctuations of a trapped particle in the trapped position [53,56–58].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the second approach, we modified the grayscale measurement method used to evaluate the time-dependent grayscale values corresponding to the upward behavior of micro-objects [ 37 , 38 ] to measure the lateral behavior of a cell, as follows. (1) During the experiment, we defined two different circular windows in the chip.…”
Section: Methodsmentioning
confidence: 99%
“…There are many important techniques used for trapping or manipulating these objects in various fields of science. These are dielectrophoretic tweezer [1], acoustic tweezer [2], magnetic tweezer [3], hydrodynamic trapping with microfluidic valving [4], optical tweezer and laser trapping [5]. Each of these techniques is suitable for different research areas and has its particular advantages or drawbacks that determine proper applications.…”
Section: Optical Tweezer System With No Fluorescent Confocal Microscomentioning
confidence: 99%